MnO2-Catalyzed electrocatalytic mineralization of triclosan in chlorinated wastewater - Asma Batool; Shan Shao; Kartick Chandra Majhi; Azeem Mushtaq; Yi Jiang; Wingkei Ho; Yiu Fai Tsang; Yuhe He; Kenneth Mei Yee Leung; Jason Chun-Ho Lam (Environmental Science and Ecotechnology, 2025)
The rising concentrations of xenobiotic aromatic compounds in the environment pose significant risks to human and ecosystem health. Developing a universal, environmentally benign, and scalable platform for mineralizing organic pollutants before their release into the environment is therefore crucial. Electrocatalysis can be highly advantageous for wastewater treatment because it is immediately responsive upon applying potential, requires no additional chemicals, and typically uses heterogeneous catalysts. However, achieving efficient electrochemical mineralization of wastewater pollutants at parts-per-million (ppm) levels remains a challenge. Here, we report the use of manganese dioxide (MnO2), an Earth-abundant, chemically benign, and cost-effective electrocatalyst, to achieve over 99% mineralization of triclosan (TCS) and other halogenated phenols at ppm levels. Two highly active MnO2 phases—α-MnO2-CC and δ-MnO2-CC—were fabricated on inexpensive carbon cloth (CC) support and evaluated for their ability to oxidatively degrade TCS in pH-neutral conditions, including simulated chlorinated wastewater, real wastewater, and both synthetic and real landfill leachates. Total organic carbon analysis confirmed the effective degradation of TCS. Electron paramagnetic resonance and ultraviolet–visible spectroscopy identified reactive oxygen species, enabling the construction of a detailed TCS degradation pathway. Upon optimization, the TCS removal rate reached 38.38 nmol min−1, surpassing previously reported rates achieved with precious and toxic metal co-catalysts. These findings highlight MnO2-CC as a promising, eco-friendly electrocatalyst with strong potential for upscaled remediation of organic pollutants in wastewater treatment.